Novel Strategies to Improve DNA Vaccine Immunogenicity - Coban, Cevayir; Kobiyama, Kouji; Aoshi, Taiki; Takeshita, Fumihiko; Horii, Toshihiro; Akira, Shizuo; J. Ishii, Ken (Current Gene Therapy, 2011)
DNA vaccines can induce both humoral and cellular immune responses in animals. Some DNA vaccines are already licensed for infectious diseases such as West Nile virus encephalitis in horses. When used in humans, however, DNA vaccines suffer from lower immunogenicity profiles. Although the reasons for this are poorly understood, various hypotheses have been proposed. This review aims to provide better understanding of the molecular and immunological mechanisms by which DNA vaccines work and how such knowledge can be used to bring about improvements in their efficacy. Recent studies have provided evidence that the ‘adjuvant effect’ of plasmid DNA is mediated by its doublestranded structure. This structure activates stimulator of interferon genes/TANK-binding kinase 1 (STING/TBK1)- dependent innate immune signaling pathways in the absence of Toll-like receptors. Indeed, type-I interferons (IFNs), induced in vivo via the STING/TBK1 pathway, were found to be crucial for both direct- and indirect-antigen presentation via distinct cell types (i.e. dendritic cells (DC) and muscle cells, respectively). Importantly, incorporation of TBK1 into a DNA vaccine was found to enhance the antigen-specific humoral immune responses targeting the Plasmodium falciparum serine repeat antigen (SERA), a candidate vaccine antigen expressed in the blood-stages of human malaria parasites. Thus, the results of these studies may offer new ways to develop DNA vaccines, as well as delivering novel vaccine adjuvants against infectious diseases.
Keywords: type I interferon